Medication abortion laws could impact public universities. (12th July 2022) - Lyerly, Eric
Abstract : States are grappling with the news that the U.S. Supreme Court overturned Roe v. Wade, the case that prohibited states from restricting abortions except under limited circumstances. ( See Dobbs v. Jackson Women's Health Organization (2022) .) Now that Roe has been overturned, states are free to make abortion illegal.